2015
DOI: 10.1042/cs20140821
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid supplementation improves microvascular function in older adults through nitric oxide-dependent mechanisms

Abstract: Older adults have reduced vascular endothelial function, evidenced by attenuated nitric oxide (NO)-dependent cutaneous vasodilatation. Folic acid and its metabolite, 5-methyltetrahydrofolate (5-MTHF), are reported to improve vessel function. We hypothesized that (i) local 5-MTHF administration and (ii) chronic folic acid supplementation would improve cutaneous microvascular function in ageing through NO-dependent mechanisms. There were two separate studies in which there were 11 young (Y: 22 ± 1 years) and 11 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
52
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 38 publications
10
52
2
1
Order By: Relevance
“…The obtained results provide arguments both for and against this possibility. Consistent with the possibility that folic acid supplementation improves cutaneous vasodilatation during heat exposure in older adults (Stanhewicz et al, 2015), greater serum folate concentrations and greater absolute values of local forearm cutaneous blood flow and vascular conductance were observed. In contrast, no effect of folic acid supplementation was observed for whole-limb forearm blood flow or vascular conductance.…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The obtained results provide arguments both for and against this possibility. Consistent with the possibility that folic acid supplementation improves cutaneous vasodilatation during heat exposure in older adults (Stanhewicz et al, 2015), greater serum folate concentrations and greater absolute values of local forearm cutaneous blood flow and vascular conductance were observed. In contrast, no effect of folic acid supplementation was observed for whole-limb forearm blood flow or vascular conductance.…”
Section: Discussionsupporting
confidence: 69%
“…Since folic acid supplementation improves nitric oxide availability (Stanhewicz & Kenney, ), it is not unreasonable to suggest that greater cutaneous blood flow/vascular conductance during local skin heating reflects improved nitric oxide availability. In support of this argument, local intradermal infusion of folic acid's active metabolite (5‐methyltetrahydrofolate) augments the nitric oxide contribution to cutaneous vasodilatation induced by local heating in healthy older adults (Stanhewicz et al., ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We previously reported that 30 m m ATP‐induced cutaneous vasodilatation is partly dependent upon by nitric oxide synthase‐ but not cyclooxygenase‐mediated mechanisms (Fujii et al., ) as assessed in a combined group of young men and women. However, several studies have demonstrated that ageing reduces nitric oxide synthase‐dependent cutaneous vasodilatation in a combined group of older men and women (Fujii et al., ; Stanhewicz, Alexander, & Kenney, ; Stanhewicz, Bruning, Smith, Kenney, & Holowatz, ). Furthermore, our previous work showed that ATP‐induced cutaneous vasodilatation at 3 m m occurred independently of nitric oxide synthase and cyclooxygenase in a combined group of young men and women (Fujii et al., ).…”
Section: Discussionmentioning
confidence: 99%